GNAS knockdown suppresses osteogenic differentiation of mesenchymal stem cells via activation of Hippo signaling pathway. Issue 12 (30th May 2019) - An, Jiangdong; Li, Guangjie; Zhang, Jin; Zhou, Haiyu; Jiang, Jin; Wang, Xingwen; Feng, Xiaofei; Wang, Shuanke
Abstract: Bone marrow‐derived mesenchymal stem cells (BMSCs) are a suitable option for cell‐based tissue engineering therapies due to their ability to renew and differentiate into multiple different tissue types, such as bone. Over the last decade, the effect of GNAS on the regulation of osteoblast differentiation has attracted great attention. Herein, this study aimed to explore the role of GNAS in osteogenic differentiation of MSCs. A total of 85 GNAS f/f male mice were selected for animal experiments and 10 GNAS f/f male mice for BMSC isolation to conduct cell experiments. The mice and BMSCs were treated with Verteporfin (a Hippo signaling pathway inhibitor) to inhibit the Hippo signaling pathway or recombinant adenovirus‐expressing Cre to knockout the GNAS expression. Next, computed tomography scan, Von Kossa staining, and alizarin red staining were performed to detect osteogenic differentiation ability. Moreover, immunohistochemistry and alkaline phosphatase (ALP) staining were used to assess the expression of Oc and Osx in femur tissues and ALP activity. At last, the expression of GNAS, osteogenic markers, and factors related to the Hippo signaling pathway was evaluated. Initially, the results displayed successful knockout of the GNAS gene from mice and BMSCs. Moreover, the data indicated that GNAS knockout inhibits expression of Oc, Osx, ALP, BMP‐2, and Runx2, and ALP activity. Additionally, GNAS knockout promotes activation of the Hippo signaling pathway, so as to repress osteogenic differentiation. Collectively, depleted GNAS exerts an inhibitory role in osteogenic differentiation of MSCs by activating Hippo signaling pathway, providing a candidate mediator for osteoporosis. Abstract : Collectively, depleted GNAS exerts an inhibitory role in osteogenic differentiation of mesenchymal stem cells by activating the Hippo signaling pathway, providing a candidate mediator for osteoporosis.